Quality improvement of recycled concrete aggregate by a large-scale tube mill with steel rod - Prasittisopin, Lapyote; Thongyothee, Chawis; Chaiyapoom, Phattarakamon; Snguanyat, Chalermwut (Journal of Asian Concrete Federation, 2018)
Research has been reported on using a steel rod in the rotary or ball mill resulting in an increase of grinding efficiency of recycled concrete aggregate (RCA). Information of the process and steel rod parameters is explored in large-scale production. In particular, energy consumption used during grinding RCA in laboratory can be misled unless the large-scale grinding production is operated. This study aims to investigate process and steel rod parameters on the performance characteristics of ground RCA (G-RCA) and its grinding energy efficiency of the large-scale rotary mill of the capacity of 500-liter per batch. The process and steel rod parameters investigated include revolution count (Rev), contacted surface area (Sa) between steel rod and RCA particle, and weight (W) of steel rod. The characteristics of the G-RCA include its gradation, yield retained on a 4.75-mm sieve, density, and water absorption. Results indicated that early grinding operation has greater efficiency to improve RCA quality and consumes less grinding energy than the later grinding operation. Grinding RCA at the Rev of 250 counts is sufficient to improve its quality for this tube mill. The grinding efficiency increased while grinding using the steel rods having higher Sa or smaller rod sizes.